DEVELOPMENT COMMUNICATION AND PARTICIPATORY TOURISM GOVERNANCE IN BOROBUDUR: A SYSTEMATIC LITERATURE REVIEW - Lovia Evanne; Dwi Retno Hapsari; Sumardjo; Dwi Sadono (Universitas Muhammadiyah Jakarta, 2025)
The development of the Borobudur National Tourism Strategic Area (NTSA) has been designated as a national priority within Indonesia’s 2020–2025 development agenda, emphasizing sustainable tourism governance and community participation in addition to infrastructure and destination promotion. In this framework, development communication functions as a strategic mechanism to connect stakeholders, enhance institutional coordination, and empower local communities. This study examines the role of development communication in shaping participatory tourism governance in national strategic areas, with Borobudur serving as an analytical reference. This research employed a systematic literature review (SLR) guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 framework. A structured search of peer-reviewed Scopus-indexed journal articles published within the last five years identified 91 records. After screening, eligibility assessment, and relevance evaluation, 12 articles were selected for in-depth synthesis. Government regulations and foundational theoretical works were also reviewed to contextualize the analysis. The selected studies were examined using thematic analysis to identify dominant themes, conceptual approaches, and governance patterns. The findings indicate that participatory communication practices, institutional transparency, and multi-stakeholder collaboration significantly influence community engagement in tourism governance. However, sectoral fragmentation, unequal power relations, and limited adaptive communication models remain persistent barriers. This study underscores development communication as a governance instrument that mediates institutional interaction and community empowerment in strategic tourism development contexts.